Who Believes the Myths? Educator Misconceptions About Giftedness Across Roles, Training, and Experience - Ercan, Merve Irem; Ziegler, Albert (Gifted education international, 2025)
Despite growing research in gifted education, myths about giftedness remain widespread among educators and may hinder appropriate support for gifted learners. In this study, data were collected from 562 participants (60.7% female, 39.3% male), including preservice teachers, in-service teachers, and university lecturers in teacher education, using the newly developed, psychometrically validated the Rapid Assessment Test of Individual Misconceptions about Giftedness (RATIMAG) instrument. This study aimed to investigate how demographic variables affect educators’ beliefs about myths about giftedness. Mann-Whitney U and Kruskal-Wallis tests revealed significant group differences based on age, education level, academic department, training in gifted education, and occupational role. Gender was not associated with belief differences. Findings emphasize the importance of sustained, role-sensitive training throughout the educator career cycle. While conducted in Türkiye, the study raises broader questions about the persistence of giftedness myths across cultures and suggests directions for improving educator preparation and policy in gifted education.
CRIS-Team Scopus Importer:2025-11-28
Keywords: cross-role comparison; educator beliefs; gifted education; misconception research; myths about giftedness; professional development; RATIMAG; teacher training